Barriers and facilitators to health care seeking behaviours in pregnancy in rural communities of southern Mozambique. Issue 1 (June 2016) - Munguambe, Khátia; Boene, Helena; Vidler, Marianne; Bique, Cassimo; Sawchuck, Diane; Firoz, Tabassum; Makanga, Prestige; Qureshi, Rahat; Macete, Eusébio; Menéndez, Clara; von Dadelszen, Peter; Sevene, Esperança
Abstract Background In countries, such as Mozambique, where maternal mortality remains high, the greatest contribution of mortality comes from the poor and vulnerable communities, who frequently reside in remote and rural areas with limited access to health care services. This study aimed to understand women's health care seeking practices during pregnancy, taking into account the underlying social, cultural and structural barriers to accessing timely appropriate care in Maputo and Gaza Provinces, southern Mozambique. Methods This ethnographic study collected data through in-depth interviews and focus group discussions with women of reproductive age, including pregnant women, as well as household-level decision makers (partners, mothers and mothers-in-law), traditional healers, matrons, and primary health care providers. Data was analysed thematically using NVivo 10. Results Antenatal care was sought at the heath facility for the purpose of opening the antenatal record. Women without antenatal cards feared mistreatment during labour. Antenatal care was also sought to resolve discomforts, such as headaches, flu-like symptoms, body pain and backache. However, partners and husbands considered lower abdominal pain as the only symptom requiring care and discouraged women from revealing their pregnancy early in gestation. Health care providers for pregnant women often included those at the health facility, matrons, elders, traditional birth attendants, and community health workers. Although seeking care from traditional healers was discouraged during the antenatal period, they did provide services during pregnancy and after delivery. Besides household-level decision-makers, matrons, community health workers, and neighbours were key actors in the referral of pregnant women. The decision-making process may be delayed and particularly complex if an emergency occurs in their absence. Limited access to transport and money makes the decision-making process to seek care at the health facility even more complex. Conclusions Women do seek antenatal care at health facilities, despite the presence of other health care providers in the community. There are important factors that prevent timely care-seeking for obstetric emergencies and delivery. Unfamiliarity with warning signs, especially among partners, discouragement from revealing pregnancy early in gestation, complex and untimely decision-making processes, fear of mistreatment by health-care providers, lack of transport and financial constraints were the most commonly cited barriers. Women of reproductive age would benefit from community saving schemes for transport and medication, which in turn would improve their birth preparedness and emergency readiness; in addition, pregnancy follow-up should include key family members, and community-based health care providers should encourage prompt referrals to health facilities, when appropriate. Trial registration NCT01911494 Resumo Antecedentes Em países como Moçambique onde a mortalidade materna permanece alta, os membros de comunidades pobres e vulneráveis, residentes em zonas rurais e remotas com acesso limitado a serviços de saúde são os que mais contribuem para esta mortalidade. O presente estudo, teve como objectivo analisar comportamentos de busca de cuidados de saúde durante a gravidez, tomando em consideração as barreiras sociais, culturais e estruturais para o acesso atempado a cuidados apropriados de saúde nas províncias de Maputo e Gaza, no Sul de Moçambique. Métodos Neste estudo etnográfico os dados foram colhidos através de entrevistas em profundidade e discussões em grupos focais com mulheres em idade reprodutiva (incluíndo mulheres grávidas), decisores ao nível do agregado familiar (parceiros, mães e sogras de mulheres grávidas), praticantes de medicina tradicional (PMTs), matronas e provedores de cuidados de saúde primários. Os dados foram analisados tematicamente usando NVivo 10. Resultados A consulta pré-natal (CPN) era procurada pelas mulheres com o fim de abrirem a ficha pré-natal, pois mulheres sem ficha temiam represálias durante o parto na unidade sanitária. A CPN era também procurada para resolver queixas comuns tais como dores de cabeça, sintomas sugestivos de gripe, dores no corpo e de coluna. No entanto, os parceiros das mulheres grávidas consideravam as dores no baixo-ventre como o único sintoma merecedor de busca de cuidados e desencorajavam as suas mulheres a revelarem a gravidez nas primeiras semanas de gestação. Os provedores de cuidados saúde para mulheres grávidas incluíam os profissionais de saúde baseados nas unidades sanitárias, mas também matronas, anciãs, parteiras tradicionais e agentes polivalentes elementares (APES). Culturalmente as mulheres grávidas são desencorajadas a buscar cuidados junto a PMTs; no entanto observou-se que PMTs prestam serviços pré- e pós- natais. Para além dos decisores ao nível do agregado familiar, as matronas, os APEs e vizinhos são actores chaves no acto de referir a mulher grávida para a unidade sanitária. O processo de tomada de decisão envolve muitos actores e pode ser moroso e complexo, particularmente em circunstâncias de emergência em que nenhum dos decisores mencionados está presente. O acesso limitado ao transporte e a fundos para custear despesas imediatas torna este processo ainda mais complexo. Conclusões As mulheres procuram cuidados pré natais de rotina nas unidades sanitárias, apesar da presença de outros provedores de saúde na comunidade. Existem factores importantes que impedem a busca de cuidados atempados e apropriados no início da gestação, bem como em situações de emergência obstétrica e parto. Fraco conhecimento dos sinais de perigo, particularmente entre os parceiros, a revelação tardia da gravidez, os processos complexos e morosos de tomada de decisão em situações de emergência, receio de maus tratos na unidade sanitária, falta de transporte e constrangimentos financeiros foram as barreiras mais mencionadas. Mulheres em idade reprodutiva poderiam beneficiar de esquemas comunitários de poupanças para transporte e medicação, que por sua vez iriam melhorar o seu grau de preparação para emergências e parto; mais ainda o seguimento da gravidez deveria envolver actores chaves no agregado familiar e vizinhança, bem como provedores de saúde baseados na comunidade, no sentido de encorajar referências atempadas à unidade sanitária sempre que necessário. Número de registo do ensaio clínico NCT01911494